2021
DOI: 10.2147/dddt.s287332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Dosage Frequency of Polymyxin B on Rat Nephrotoxicity

Abstract: Background Polymyxin B, as the final treatment against multidrug-resistant Gram-negative bacilli, is widely used in clinical practice. However, little is known about the nephrotoxicity of polymyxin B. The purpose of this study was to elucidate the relationship between polymyxin B nephrotoxicity and daily administration frequency. Methods Sprague–Dawley rats were randomly divided into three groups: 18 mg/kg/q24 h group (Group A, once daily), 9 mg/kg/q12 h group (Group B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…rats receiving fractionated dosing schemes had slightly higher degrees of kidney injury than those receiving once daily administration. 14,15 AKI was very common in all of the human and preclinical studies, and kidney injury rates and extents were reasonably similar between groups. Thus, it is unlikely that toxicity will be ameliorated by simply changing the dosing scheme (of the same total daily dose); attention must be focused on early identification and prevention of toxicity.…”
Section: Introductionmentioning
confidence: 82%
“…rats receiving fractionated dosing schemes had slightly higher degrees of kidney injury than those receiving once daily administration. 14,15 AKI was very common in all of the human and preclinical studies, and kidney injury rates and extents were reasonably similar between groups. Thus, it is unlikely that toxicity will be ameliorated by simply changing the dosing scheme (of the same total daily dose); attention must be focused on early identification and prevention of toxicity.…”
Section: Introductionmentioning
confidence: 82%
“…One study in rats showed that polymyxin=-induced nephrotoxicity was related to the frequency of dosing [28]. A 10-year cohort study found that nephrotoxicity is related to the dose and the number of days of administration [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it also protonates under physiological conditions and interacts with phosphate anions in the cell membranes of healthy cells, especially in the kidney, where PMB accumulates. 7 That is the most critical mechanism of PMB-induced nephrotoxicity: PMB increases the permeability of tubular epithelial cell membranes, leading to an influx of cations, anions and water. 8 In the last two decades of the twentieth century, several approaches have been used to encapsulate PMB through electrostatic interactions, shielding the cationic portion or reducing the number of cationic residues.…”
Section: Introductionmentioning
confidence: 99%